The impact of public procurement governance in the face of corruption - Rebai, Manal; معلم يوسف (Journal of Human Sciences, 2022)
The Algerian legislator has devoted the principles of governance in the field of public procurement in an effort to provide an appropriate legal system that guarantees and secures the efficiency of the public deal, as well as protecting it from aspects of corruption.